A key of success to Empty Fruit Bunches, POME and water sludge: Composting - Kabbashi, Nassereldeen Ahmed; Mirghani, Mohamed Elwathig Saeed; Keya Nordin, Masturah (2013)
Palm oil production is a major industry in Malaysia, in which oil palm empty fruit bunches (EFB) and palm oil mill effluent (POME) are considered as major waste products. Besides that, drinking water treatment process produced water sludge in large amount every day. These waste products create environmental pollution and required high disposal costs every year. Bio composting is an environmentally method where its product could be utilized as plant growth enhancement. Success keys to this simple composting process are EFB, POME, and water sludge as the substrates and the co-substrate is sawdust. The strains of Phanerochaete chrysosporium, Trichoderma reesei, Aspergillus niger and Penicillium are used in this experiment to help the degradation of the wastes. Tray bioreactor was used to test the efficiency of the composting process. The composting period for this process was 60 days and some parameters were determined to evaluate the compost quality. The maturity of the composting could be reflecting by C/N ratio and germination index result. From the experiment, the results shown that the optimum condition for composting process were found to be at pH5, inoculums dosage 5% and particle size of EFB 2mm.